Efeito da nutrição com cálcio e potássio na severidade da mancha aureolada (Pseudomonas syringae pv. garcae) do cafeeiro (Coffea arabica) - Carvalho, Nathan Moura (2016)
The target spot of coffee plants, caused by Pseudomonas syringae pv. garcea, had great destructive potential. Nutrients such as calcium (Ca) and Potassium (K) are frequently studied in many pathosystems, for being related to the defense barriers of the plant. Thus, the objective of this study was to evaluate the effect of different doses of Ca and K over the incidence and severity of the target spot in coffee seedlings cultivated in nutritive solution. The treatments consisted of five doses of Ca (0.5, 3, 6, 9 and 12 mmon.L-1) combined with five doses of K (0.5, 3, 7, 12 and 15 mmol.L-1) in a factorial scheme. Plants of the Catuaí Vermelho IAC 99 cultivar were cultivated in Hoagland nutritive solution, altering only the doses of Ca and K, according to the treatment. The bacteria was inoculated by pulverization and, when the first symptoms emerged, we evaluated the severity of the disease with the aid of diagram scale, Posteriorly calculating the area beneath the progression curve of the severity of all combinations of Ca and K. Calcium doses inferior to 3 mmol.L-1, regardless of the doses of K and the combinations of the doses of Ca and K, both above 8 mmol.L-1, provided greater severity of the target spot. While the doses of Ca between 6 and 10 mmol.L-1, combined with doses of K between 4 and 8 mmol.L-1, provided low disease severity, higher accumulation of dry matter and lower contents of Nitrogen in the foliar tissue.